STRATEGIES FOR THE PREVENTION OF FACIAL PRESSURE INJURIES CAUSED BY THE USE OF THE PRONE POSITION (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: Identify the main strategies for preventing facial pressure injuries caused by the use of the prone position. Methods: Integrative literature review, carried out during the month of March 2021. Articles were searched in the MEDLINE, LILACS, BDENF and IBECS databases. The selected articles were written in English, Portuguese and Spanish, between 2016 and 2021. Duplicates and those that did not include the topic addressed were excluded. Initially, 29 articles were identified. After applying the inclusion and exclusion criteria, 10 articles resulted for analysis. Results: Of the complications related to the use of the prone position, 10 (100%) of the studies address the pressure injury as the main complication of this therapeutic maneuver. As for prevention strategies, the studies analyzed cite the change in position associated with the use of pads and hydrocolloids as the main preventive methods. Conclusion: The following strategies to prevent facial pressure injury by using the prone position were identified: change of decubitus at pre-established times; use of devices that provide relief from pressure points, such as pads and hydrocolloids; and the use of low-cost and easily accessible materials, such as adapted surgical sponges, respecting the anatomical structures of each patient.